Compositional characteristics of red clover (Trifolium pratense) seeds and supercritical CO2 extracted seed oil as potential sources of bioactive compounds - Zhou, Ying (Maximum Academic Press, 2025)
Plant seeds from the Fabaceae (Leguminosae) family are commonly edible. However, little has been done to study the phytochemicals of red clover (Trifolium pratense) seeds. Our study aims to obtain comprehensive and novel findings on red clover seeds and supercritical fluid extraction (SFE)-extracted oil, with the purpose of exploring their potential as a new source of functional ingredients for food and health care products. In our study, red clover seed oil was extracted by supercritical CO2. Forty-four phytochemical compounds were preliminarily identified in red clover seeds and the extracted oil by UPLC-ESI-MS/MS metabolomics method. These compounds mainly belong to lipids, phenolic compounds, terpenoids and phytosterols. Red clover seeds contain fatty acids (4,676.1 mg/100 g dried seeds) and bioactive components such as phenolic compounds (228.4 mg/100 g) and tocopherols (94.9 mg/100 g). In red clover seed oil, unsaturated fatty acids are over 83% and are rich in linoleic acid (54.7 g/100 g oil) and oleic acid (14.0 g/100 g oil). These findings provide important guidance for introducing red clover seed oil into pharmaceutical products or as functional foods.